The untold story of primary alveolar soft part sarcoma of the fibula: A rare case report with review of the literature - Singh, Vasudha; Bhargava, Mudita; Kumar, Varsha; Misra, Vatsala (Indian Journal of Case Reports, 2020)
Alveolar soft part sarcoma (ASPS) is a rare soft-tissue tumor occurring in skeletal muscles or musculofascial planes with an incidence of 0.5–1%. In adults, the lower extremity is most commonly involved, whereas in children, the involvement of the head-and-neck region is more common. Metastasis to the brain, bone, and lungs is common; however, primary bone involvement is extremely rare. We report the case of a 25-year-old male who presented with a painless slowly progressive swelling in the left lower limb for 1 year with no history of trauma. The case was diagnosed as primary ASPS of the fibula after ruling out the involvement of soft tissue and other organs. To the best of our knowledge, only 11 cases of primary ASPS of bone have been reported so far.